Preparation process of high-elasticity pressure-resistant air-permeable and water-permeable sponge

Through the combination of specific components and processes, the problems of pore closure and decreased moisture permeability in the improvement of sponge mechanical properties were solved, and a sponge with high elasticity, pressure resistance, air permeability and water permeability was prepared, which is suitable for a variety of application scenarios.

CN120737405APending Publication Date: 2025-10-03HUBEI XINJIAYUAN IND & TRADE CO LTD

Patent Information

Application Number
CN202511055259.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

When improving the mechanical properties of sponges, existing technologies easily lead to closure of pores, decreased moisture permeability, uneven dispersion of nanofillers, limited reinforcement effects, and easy clogging of pore channels.

Method used

A high-elastic, pressure-resistant, breathable and water-permeable sponge is prepared by mixing components such as highly branched polyester polyols, polyether polyols, isocyanate, multi-walled carbon nanotubes, nano-silica, montmorillonite, and silane coupling agents, combined with processes such as step-by-step dehydration, pulse injection, gradient foaming, microwave irradiation, and chemical etching.

Benefits of technology

It achieves high elasticity, pressure resistance, air permeability and water permeability of the sponge, improves compression strength and fatigue resistance, cell uniformity and moisture permeability, and is suitable for the needs of different fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120737405A_ABST
    Figure CN120737405A_ABST
Patent Text Reader

Abstract

The invention provides a preparation process of a high-elastic pressure-resistant air-permeable and water-permeable sponge. The sponge is prepared from the following components in parts: 40 to 60 parts of highly branched polyester polyol, 37 to 43 parts of polyether polyol, 50 to 56 parts of isocyanate, 1.5 parts of multiwalled carbon nanotubes, 2.0 parts of nano silicon dioxide, 1.0 part of montmorillonite, 0.54 to 0.7 part of silane coupling agent, 2.0 to 3.1 parts of polyethylene glycol and 0.8 part of bimetallic catalyst. 1.8 parts of a foaming agent, 15 parts of a supercritical agent and 1.2 parts of an opening agent; the preparation method comprises the following steps: S1, carrying out segmented vacuum dehydration on highly branched polyester polyol and polyether polyol, carrying out xylene ultrasonic treatment on multi-walled carbon nanotubes and a silane coupling agent, and carrying out high-shear mixing to prepare a nanofiller dispersion liquid; through step-by-step dehydration, polyol thermal degradation is reduced, the hydroxyl value retention rate is improved, the integrity of a cross-linked network is ensured, through step-by-step dehydration and magnetic field dispersion, the problems of polyol thermal degradation and nano agglomeration are solved, and superuniform dissolution and precise regulation and control of double-peak aperture are realized through pulse injection and magnetic field coupling foaming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sponge preparation, and in particular to a process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge. Background Art

[0002] At present, sponge materials are widely used in medical, sports, industrial sealing and other fields, and their performance optimization mainly revolves around density, mechanical strength and air permeability.

[0003] Patent publication number CN111040123A discloses a method for preparing a polyurethane filter sponge, belonging to the field of polyurethane foaming. The method comprises components A and B in the following weight proportions: Component A: 30-70 parts polyether polyol; 5-10 parts polymer polyol; 25-65 parts polyether polyol; 1.5-3.5 parts water; 0.8-1.5 parts foam stabilizer; 0.05-0.4 parts tin catalyst; 0.1-0.4 parts amine catalyst; and Component B: 20-50 parts TDI (T-80). The invention also provides a simple and easy-to-implement preparation method. The method features a simple process, high production efficiency, low cost, and advantages such as high porosity, good air and water permeability, excellent flexibility, high tensile strength, and high tear resistance.

[0004] Based on the aforementioned comparative documents and analysis of traditional high-density sponges, increasing the isocyanate crosslink density or reducing the amount of blowing agent can achieve this. However, such methods can easily lead to cell closure and a significant decrease in moisture permeability (typically <5000g / (m²・day)). To enhance mechanical properties, existing technologies often add nanofillers, but due to limitations in the dispersion process, agglomeration is common, resulting in limited reinforcement and a tendency to clog cell channels. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the defects of the prior art. The present invention proposes a preparation process for a high-elasticity, pressure-resistant, breathable and water-permeable sponge.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge, which is prepared according to the following components and quantities:

[0007] 40-60 parts of high-branched polyester polyol, 37-43 parts of polyether polyol, 50-56 parts of isocyanate, 1.5 parts of multi-walled carbon nanotubes, 2.0 parts of nano-silica, 1.0 parts of montmorillonite, 0.54-0.7 parts of silane coupling agent, 2.0-3.1 parts of polyethylene glycol, 0.8 parts of bimetallic catalyst, 1.8 parts of foaming agent, supercritical carbon dioxide, 1.5 parts of carbon nanotubes, 2.0 parts of nano-silicon dioxide, 1.0 parts of montmorillonite, 0.54-0.7 parts of silane coupling agent, 2.0-3.1 parts of polyethylene glycol, 0.8 parts of bimetallic catalyst, 1.8 parts of foaming agent, supercritical carbon dioxide, 1.5 parts of carbon nanotubes, 2.0 parts of nano-silicon dioxide, 1.0 parts of montmorillonite, 0.54-0.7 parts of silane coupling agent, 2.0-3.1 parts of polyethylene glycol, 0.8 parts of bimetallic catalyst, 1.8 parts of foaming agent, supercritical carbon dioxide, 1.5 parts of carbon nanotubes, 1.5 ...1.0 parts of silane coupling agent, 0.54-0.7 parts of silane coupling agent, 0.54-0.7 parts of silane coupling agent, 0.54-0.7 parts of silane coupling 15 parts, 1.2 parts of pore opening agent;

[0008] S1: Raw material pretreatment and premixing, high-branched polyester polyol and polyether polyol according to Mix in proportion and place in a vacuum drying oven. In the first stage, dehydrate at 100 degrees Celsius and -0.095Mpa for 1 hour. In the second stage, cool to 80 degrees Celsius and continue dehydrating for 1 hour to control the moisture content. ;

[0009] Multi-walled carbon nanotubes, montmorillonite and silane coupling agent were prepared according to Xylene was added in a ratio of 1:1 to 1:1, and ultrasonic treatment was performed at 40 kHz and 300 W for 15 minutes. The dispersion was poured into the polyol and treated with a high shear mixer for 10 minutes to form a nanofiller dispersion.

[0010] Add in high-speed stirring kettle:

[0011] 100 parts of dehydrated polyol;

[0012] 4.5 parts of nanofiller dispersion;

[0013] 3 parts of polyethylene glycol;

[0014] catalyst, , 0.8 parts;

[0015] 1.2 parts of cell-opening agent polyether surfactant;

[0016] Stir at 500 rpm for 5 minutes, followed by mixing at 2500 rpm for 3 minutes;

[0017] S2: Dynamic foaming, pulsed in a high-pressure reactor Injection, first injection of liquid 5 parts, pressurize to 15MPa, maintain for 30 seconds, and inject the second 5 parts, pressurize to 20MPa, maintain for 30 seconds, and inject a third 5 parts, pressurized to 25MPa, maintained for 30 seconds, and simultaneously applied a pulsed magnetic field to promote dissolve;

[0018] Gradient foaming control, at 50 ° C, 25 MPa, maintained for 3 minutes, adding 0.05% nano calcium carbonate to promote heterogeneous nucleation, then linearly heating to 80 ° C, rate 5 ° C / min, reducing pressure to 10 MPa, while applying axial tensile stress, strain rate , expand, and finally quench by liquid nitrogen spray to fix the shape. When the expansion rate is 70%, the glass fiber mesh pre-coated with polyurethane is embedded by electrostatic adsorption, and 0.1MPa air pressure is applied to compact it and the pressure is maintained for 5 minutes;

[0019] S3: Curing treatment, 2450MHz microwave irradiation for 8 minutes, switch to 915MHz microwave treatment for 12 minutes, spray Sol, containing 0.2% graphene quantum dots, UV-cured for 5 minutes;

[0020] S4: Opening treatment: After needle rolling, ultrasonic treatment is immediately performed, followed by chemical etching and immersion in 0.1% hydrofluoric acid solution for 30 seconds.

[0021] Furthermore, the first stage dehydration conditions in S1 are temperature 100°C, vacuum degree -0.095MPa, and time 1 hour; the second stage dehydration conditions are temperature 80°C, vacuum degree -0.08MPa, and time 1 hour, and the final polyol moisture content is ≤0.02wt%.

[0022] Furthermore, during the foaming stage, a laser particle size analyzer detects the cell size distribution online, and in the subsequent curing stage, an infrared thermal imager monitors the uniformity of the temperature field and automatically adjusts the microwave power.

[0023] Further, the sponge is placed in a supercritical The reaction mixture was treated at a pressure of 8 MPa and a temperature of 40°C for 1 hour to remove residual catalyst and oligomers.

[0024] Furthermore, the mass ratio of multi-walled carbon nanotubes, montmorillonite and silane coupling agent in the nanofiller dispersion is , and the ultrasonic treatment parameters are: frequency 40 kHz, power 300 W, time 15 min, high shear mixer speed 8000 rpm, shear time 10 min.

[0025] Furthermore, the pulse injection in S2 The magnetic field parameters are: pulse frequency 10 Hz, magnetic field intensity 0.5 T, and an axial alternating magnetic field is applied during the pressure holding stage after each injection, with the magnetic field direction forming an angle of 30° with the axis of the reactor.

[0026] Furthermore, in the gradient foaming control, the particle size of the heterogeneous nucleating agent nano calcium carbonate is 20-50 nm, and the addition amount is 0.05-0.1% of the total mass of the polyol; the axial tensile strain rate is , the stretching direction is perpendicular to the fiber web plane.

[0027] Furthermore, the microwave irradiation parameters in S3 are: 2450MHz, power density 2.5W / g, time 8min in the first stage; 915MHz, power density 1.2W / g, time 12min in the second stage; UV curing wavelength is 365nm, irradiation intensity .

[0028] Furthermore, the concentration of graphene quantum dots in the spray sol is 0.1-0.3 wt %, the particle size is 2-5 nm, and the sol carrier is a mixed solvent consisting of ethanol and deionized water in a volume ratio of 3:1.

[0029] Furthermore, the chemical etching solution is a mixed acid solution composed of hydrofluoric acid and nitric acid in a volume ratio of 1:3, with a total concentration of 0.05-0.15wt%, an etching time of 30-60s, and is immediately neutralized and rinsed with a sodium bicarbonate solution with a pH of 8.5 after etching.

[0030] Compared to existing technologies, the present invention offers several advantages: In the first stage, the temperature is controlled at 100°C, and a vacuum of -0.095 MPa is maintained for one hour of dehydration. This stage primarily removes the majority of the free water in the polyol. Because the temperature is relatively low, it effectively prevents the polyol from experiencing severe thermal degradation in the presence of large amounts of water. The second stage then lowers the temperature to 80°C, adjusts the vacuum to -0.08 MPa, and dehydrates for another hour. This stage primarily removes bound water from the polyol, and the lower temperature further reduces the potential for thermal degradation. This step-by-step dehydration method significantly improves the hydroxyl value retention of the polyol, achieving a hydroxyl value retention rate exceeding 90%. This high hydroxyl value retention ensures sufficient reactive groups in the polyol are available for subsequent crosslinking reactions, thereby forming a complete, uniform, and stable crosslinked network. The resulting sponge exhibits improved mechanical properties, such as higher compressive strength, improved elasticity, and fatigue resistance, enabling it to withstand more demanding environments and extend its service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The disclosure of the present invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. In the accompanying drawings, the same reference numerals are used to refer to the same components. Among them:

[0032] Figure 1 A schematic diagram of a process flow for preparing a highly elastic, pressure-resistant, breathable and water-permeable sponge according to one embodiment of the present invention is shown; DETAILED DESCRIPTION

[0033] It is easy to understand that according to the technical solution of the present invention, without changing the essential spirit of the present invention, a person skilled in the art can propose a variety of interchangeable structural modes and implementation modes. Therefore, the following specific embodiments and drawings are only exemplary descriptions of the technical solution of the present invention and should not be regarded as the entire invention or as a limitation or restriction of the technical solution of the present invention.

[0034] According to one embodiment of the present invention, Figure 1 Shows:

[0035] Example 1:

[0036] 50 parts of highly branched polyester polyol, 43 parts of polyether polyol, 50 parts of isocyanate, 1.5 parts of multi-walled carbon nanotubes, 2.0 parts of nano-silica, 1.0 part of montmorillonite, 0.54 parts of silane coupling agent, 2.0 parts of polyethylene glycol, and a bimetallic catalyst , 0.8 parts, foaming agent 1.8 parts, supercritical 15 parts, 1.2 parts of cell opener polyether surfactant.

[0037] Mix the highly branched polyester polyol and polyether polyol and place them in a vacuum drying oven. In the first stage, dehydrate them at 100°C and a vacuum of -0.095 MPa for 1 hour. In the second stage, dehydrate them at 80°C and a vacuum of -0.08 MPa for 1 hour, ultimately reducing the water content of the polyol to ≤0.02 wt%.

[0038] Preparation of nanofiller dispersion: Multi-walled carbon nanotubes, montmorillonite, and silane coupling agent were mixed in a certain mass ratio, xylene was added, and ultrasonic treatment was performed at a frequency of 40 kHz and a power of 300 W for 15 minutes. Then, a high shear mixer was used at a speed of 8000 rpm for 10 minutes to prepare a nanofiller dispersion;

[0039] The raw materials were mixed, and the dehydrated polyol, nanofiller dispersion, and polyethylene glycol were added to a high-speed stirring kettle, stirred at 500 rpm for 5 minutes, and then mixed at 2500 rpm for 3 minutes.

[0040] Pulsed injection supercritical :Inject supercritical water into the high pressure reactor in three pulses 5 portions are injected each time, with pressures of 15MPa, 20MPa, and 25MPa, respectively, maintained for 30 seconds each. A pulsed magnetic field with a pulse frequency of 10Hz and a magnetic field strength of 0.5T is applied during injection. An axial alternating magnetic field is applied during the pressure holding stage after each injection, with the magnetic field direction forming a 30° angle with the axis of the reactor.

[0041] Gradient foaming control, maintain at 50℃, 25MPa for 3 minutes, add nano calcium carbonate with a particle size of 20-50nm and an addition amount of 0.05% of the total weight of polyol to form nuclei. Linearly increase the temperature to 80℃, reduce the pressure to 10MPa, and at the same time The fiber mesh is expanded by applying tensile stress perpendicular to its plane at an axial tensile strain rate of 100 nm, and then quenched with liquid nitrogen spray to set the shape. When the foaming expansion rate reaches 70%, it is embedded into the pre-coated polyurethane glass fiber mesh through electrostatic adsorption and compacted with 0.1 MPa air pressure to maintain pressure. During the foaming process, a laser particle size analyzer is used to measure the cell size distribution online.

[0042] For curing and hole opening, the curing process was first performed with microwave irradiation at 2450 MHz and a power density of 2.5 W / g for 8 minutes, followed by microwave treatment at 915 MHz and a power density of 1.2 W / g for 12 minutes. During the curing phase, an infrared thermal imager was used to monitor the temperature uniformity and automatically adjust the microwave power.

[0043] The pores were opened mechanically, and then ultrasonically assisted. The pores were then immersed in a mixed acid solution of hydrofluoric acid and nitric acid with a volume ratio of 1:3 and a total concentration of 0.05 wt% for etching for 30 s. After etching, the pores were immediately neutralized and rinsed with a sodium bicarbonate solution with a pH of 8.5.

[0044] Surface treatment: spraying a sol with a graphene quantum dot concentration of 0.1wt% and a particle size of 2-5nm (the sol carrier is a mixed solvent consisting of ethanol and deionized water in a volume ratio of 3:1), using a wavelength of 365nm and an irradiation intensity of UV curing, the sponge is placed in a supercritical fluid with a pressure of 8MPa and a temperature of 40℃ Treat at room temperature for 1 hour to remove residual catalyst and oligomers.

[0045] Example 2:

[0046] 50 parts of highly branched polyester polyol, 40 parts of polyether polyol, 53 parts of isocyanate, 1.5 parts of multi-walled carbon nanotubes, 2.0 parts of nano-silica, 1.0 parts of montmorillonite, 0.6 parts of silane coupling agent, 2.5 parts of polyethylene glycol, and a bimetallic catalyst , 0.8 parts, foaming agent 1.8 parts, supercritical 15 parts, 1.2 parts of cell-opening agent polyether surfactant

[0047] Mix the highly branched polyester polyol and polyether polyol and place them in a vacuum drying oven. In the first stage, dehydrate them at 100°C and a vacuum of -0.095 MPa for 1 hour. In the second stage, dehydrate them at 80°C and a vacuum of -0.08 MPa for 1 hour, ultimately reducing the water content of the polyol to ≤0.02 wt%.

[0048] Preparation of nanofiller dispersion: Multi-walled carbon nanotubes, montmorillonite, and silane coupling agent were mixed in a certain mass ratio, xylene was added, and ultrasonic treatment was performed at a frequency of 40 kHz and a power of 300 W for 15 minutes. Then, a high shear mixer was used at a speed of 8000 rpm for 10 minutes to prepare a nanofiller dispersion;

[0049] The raw materials were mixed and the dehydrated polyol, nanofiller dispersion, and polyethylene glycol were added to a high-speed stirring kettle and stirred at 500 rpm for 5 minutes, followed by 2500 rpm for 3 minutes. The highly branched polyester polyol and polyether polyol were mixed and placed in a vacuum drying oven. In the first stage, dehydration was performed at 100°C and a vacuum of -0.095 MPa for 1 hour. In the second stage, dehydration was performed at 80°C and a vacuum of -0.08 MPa for 1 hour, ultimately reducing the polyol moisture content to ≤0.02 wt%.

[0050] Preparation of nanofiller dispersion: Multi-walled carbon nanotubes, montmorillonite, and silane coupling agent were mixed in a certain mass ratio, xylene was added, and ultrasonic treatment was performed at a frequency of 40 kHz and a power of 300 W for 15 minutes. Then, a high shear mixer was used at a speed of 8000 rpm for 10 minutes to prepare a nanofiller dispersion;

[0051] The raw materials were mixed, and the dehydrated polyol, nanofiller dispersion, and polyethylene glycol were added to a high-speed stirring kettle, stirred at 500 rpm for 5 minutes, and then mixed at 2500 rpm for 3 minutes.

[0052] Pulsed injection supercritical :Inject supercritical water into the high pressure reactor in three pulses 5 portions are injected each time, with pressures of 15MPa, 20MPa, and 25MPa, respectively, maintained for 30 seconds each. A pulsed magnetic field with a pulse frequency of 10Hz and a magnetic field strength of 0.5T is applied during injection. An axial alternating magnetic field is applied during the pressure holding stage after each injection, with the magnetic field direction forming a 30° angle with the axis of the reactor.

[0053] Gradient foaming control, maintain at 50℃, 25MPa for 3 minutes, add nano calcium carbonate with a particle size of 20-50nm and an addition amount of 0.07% of the total weight of polyol to form nuclei. Linearly increase the temperature to 80℃, reduce the pressure to 10MPa, and at the same time The fiber mesh is expanded by applying tensile stress perpendicular to its plane at an axial tensile strain rate of 100 nm. Liquid nitrogen spray is then used to quench and set the shape. When the expansion rate reaches 70%, it is embedded into a pre-coated polyurethane fiberglass mesh via electrostatic adsorption and compacted with 0.1 MPa air pressure. During the foaming process, a laser particle size analyzer is used to measure the cell size distribution online.

[0054] For curing and hole opening, the curing process was first performed with microwave irradiation at 2450 MHz and a power density of 2.5 W / g for 8 minutes, followed by microwave treatment at 915 MHz and a power density of 1.2 W / g for 12 minutes. During the curing phase, an infrared thermal imager was used to monitor the temperature uniformity and automatically adjust the microwave power.

[0055] The samples were first mechanically opened, then ultrasonically assisted, and then immersed in a mixed acid solution of hydrofluoric acid and nitric acid with a volume ratio of 1:3 and a total concentration of 0.1 wt% for etching for 45 seconds. After etching, they were immediately neutralized and rinsed with sodium bicarbonate solution with a pH of 8.5.

[0056] Spraying graphene quantum dot concentration of 0.2wt% and particle size of 2-5nm sol (sol carrier is a mixed solvent composed of ethanol and deionized water in a volume ratio of 3:1), using a wavelength of 365nm and an irradiation intensity of UV curing;

[0057] The sponge was placed in a supercritical fluid with a pressure of 8 MPa and a temperature of 40°C. Treat at room temperature for 1 hour to remove residual catalyst and oligomers.

[0058] Example 3:

[0059] 60 parts of highly branched polyester polyol, 37 parts of polyether polyol, 56 parts of isocyanate, 1.5 parts of multi-walled carbon nanotubes, 2.0 parts of nano-silica, 1.0 parts of montmorillonite, 0.7 parts of silane coupling agent, 3.1 parts of polyethylene glycol, and a bimetallic catalyst , 0.8 parts, foaming agent 1.8 parts, supercritical 15 parts, 1.2 parts of cell-opening polyether surfactant;

[0060] Mix the highly branched polyester polyol and polyether polyol and place them in a vacuum drying oven. In the first stage, dehydrate them at 100°C and a vacuum of -0.095 MPa for one hour. In the second stage, dehydrate them at 80°C and a vacuum of -0.08 MPa for one hour, ultimately reducing the polyol's moisture content to ≤0.02 wt%.

[0061] Nanofiller dispersion was prepared by mixing multi-walled carbon nanotubes, montmorillonite, and silane coupling agent in a certain mass ratio, adding xylene, and ultrasonically treating the mixture at a frequency of 40 kHz and a power of 300 W for 15 minutes, and then treating the mixture with a high shear mixer at a speed of 8000 rpm for 10 minutes to prepare a nanofiller dispersion.

[0062] Raw material mixing: Add the dehydrated polyol, nanofiller dispersion, and polyethylene glycol into a high-speed stirring kettle, stir at 500 rpm for 5 minutes, and then mix at 2500 rpm for 3 minutes.

[0063] Pulsed injection supercritical :Inject supercritical water into the high pressure reactor in three pulses 5 portions are injected each time, with pressures of 15MPa, 20MPa, and 25MPa, respectively, maintained for 30 seconds each. A pulsed magnetic field with a pulse frequency of 10Hz and a magnetic field strength of 0.5T is applied during injection. An axial alternating magnetic field is applied during the pressure holding stage after each injection, with the magnetic field direction forming a 30° angle with the axis of the reactor.

[0064] Maintain the temperature at 50℃ and 25MPa for 3 minutes, add nano calcium carbonate with a particle size of 20-50nm and an addition amount of 0.1% of the total weight of the polyol to form nuclei. Linearly increase the temperature to 80℃ and reduce the pressure to 10MPa. The fiber mesh is expanded by applying tensile stress perpendicular to its plane at an axial tensile strain rate of 100 nm. Liquid nitrogen spray is then used to quench and set the shape. When the expansion rate reaches 70%, it is embedded into a pre-coated polyurethane fiberglass mesh via electrostatic adsorption and compacted with 0.1 MPa air pressure. During the foaming process, a laser particle size analyzer is used to measure the cell size distribution online.

[0065] The curing process was performed using microwaves at 2450 MHz and a power density of 2.5 W / g for 8 minutes, followed by microwaves at 915 MHz and a power density of 1.2 W / g for 12 minutes. During the curing phase, an infrared thermal imager was used to monitor the temperature uniformity and automatically adjust the microwave power.

[0066] First, mechanical opening is performed, followed by ultrasonic assisted treatment, and then the surface is immersed in a mixed acid solution composed of hydrofluoric acid and nitric acid in a volume ratio of 1:3 and a total concentration of 0.15wt% for etching for 60s. After etching, it is immediately neutralized and rinsed with a sodium bicarbonate solution with a pH of 8.5.

[0067] Spraying graphene quantum dot concentration of 0.3wt% and particle size of 2-5nm sol (sol carrier is a mixed solvent composed of ethanol and deionized water in a volume ratio of 3:1), using a wavelength of 365nm and an irradiation intensity of UV curing.

[0068] Post-treatment: Place the sponge in a supercritical fluid at a pressure of 8 MPa and a temperature of 40°C. Treat at room temperature for 1 hour to remove residual catalyst and oligomers.

[0069] Comparisons are made between the above-mentioned Examples 1, 2 and 3 and the prior art based on key performance indicators and process parameters:

[0070] Performance indicators Existing technology Example 1 Example 2 Example 3 Raw material ratio 40 parts of highly branched polyester 50 parts of highly branched polyester 60 parts of highly branched polyester 43 parts of polyether 40 parts of polyether 37 parts of polyether Density (kg / m³) 200-250 250 270 280 Moisture permeability (g / (m²・day)) 4000-6000 8500 8800 9000 Compression strength (MPa) 1.5-2.0 2.5 2.8 3.2 Opening rate (%) 85-90 98.5 98.7 98.9 Antibacterial rate (%) 99-99.5 99.99 99.995 99.999 Cell size (μm) 20-50 (standard deviation > 30%) 15 (standard deviation 12%) 13 (standard deviation 10%) 12 (standard deviation 8%) Interface bonding strength (MPa) <5 8 8.5 9 <![CDATA[Carbon footprint (kgCO2 / kg)]]> Baseline value 12% reduction 15% reduction Reduce by 10% Cost (relative value) 100% 85% 82% 88%

[0071] Key difference analysis: Example 1 has the lowest proportion of high-branched polyester and the density , moisture permeability , suitable for medical fields with high requirements for moisture permeability, Example 3: The proportion of high-branched polyester is the highest, and the density , the moisture permeability still reaches , suitable for industrial seals that require high-strength support;

[0072] In mechanical performance improvement example 3: nano filler dispersion is better (silane coupling agent 0.7 parts), compressive strength is 3.2MPa, which is improved compared with the existing technology , then Example 3 by Graphene quantum dots+ Coating, antibacterial rate , far exceeding the existing technology. Cell uniformity: Example 3 uses a pulsed magnetic field Nano calcium carbonate, the standard deviation of pore size is only , for the existing technology .

[0073] In Example 2, the proportion of bio-based raw materials added is the highest, and the carbon footprint is reduced , the lowest cost .

[0074] Example 2: Best overall performance, density , moisture permeability , cost reduction , suitable for large-scale industrial production.

[0075] Example 3: Extreme Performance, Density , moisture permeability , antibacterial rate , suitable for high-end medical and aviation fields.

[0076] Example 1: Balanced, density , moisture permeability , the lowest cost, suitable for cost-sensitive scenarios such as sports protective gear.

[0077] Through segmented dehydration and pulsed magnetic field, it has broken through the performance bottleneck of traditional sponges and has significant technical advantages and market competitiveness.

[0078] The technical scope of the present invention is not limited to the contents of the above description. Those skilled in the art can make various deformations and modifications to the above embodiments without departing from the technical idea of ​​the present invention, and these deformations and modifications should all fall within the protection scope of the present invention.

Claims

1. A process for preparing a high-elastic, pressure-resistant, breathable and water-permeable sponge, characterized in that: Prepare according to the following ingredients and quantities: 40-60 parts of high-branched polyester polyol, 37-43 parts of polyether polyol, 50-56 parts of isocyanate, 1.5 parts of multi-walled carbon nanotubes, 2.0 parts of nano-silica, 1.0 parts of montmorillonite, 0.54-0.7 parts of silane coupling agent, 2.0-3.1 parts of polyethylene glycol, 0.8 parts of bimetallic catalyst, 1.8 parts of foaming agent, supercritical carbon dioxide, 1.5 parts of carbon nanotubes, 2.0 parts of nano-silicon dioxide, 1.0 parts of montmorillonite, 0.54-0.7 parts of silane coupling agent, 2.0-3.1 parts of polyethylene glycol, 0.8 parts of bimetallic catalyst, 1.8 parts of foaming agent, supercritical carbon dioxide, 1.5 parts of carbon nanotubes, 2.0 parts of nano-silicon dioxide, 1.0 parts of montmorillonite, 0.54-0.7 parts of silane coupling agent, 2.0-3.1 parts of polyethylene glycol, 0.8 parts of bimetallic catalyst, 1.8 parts of foaming agent, supercritical carbon dioxide, 1.5 parts of carbon nanotubes, 1.5 ...1.0 parts of silane coupling agent, 0.54-0.7 parts of silane coupling agent, 0.54-0.7 parts of silane coupling agent, 0.54-0.7 parts of silane coupling 15 parts, 1.2 parts of pore opening agent; S1: The highly branched polyester polyol and polyether polyol are vacuum dehydrated in sections, and the multi-walled carbon nanotubes and silane coupling agent are ultrasonicated in xylene and then high-shear mixed to prepare a nanofiller dispersion; the dehydrated polyol, nanofiller dispersion, and polyethylene glycol are then mixed, first stirred at 500 rpm for 5 minutes, and then at 2500 rpm for 3 minutes; S2: Dynamic foaming, pulse injection of supercritical fluid into the high-pressure reactor , injected three times, 5 parts each time, with pressures of 15MPa, 20MPa and 25MPa, each maintained for 30 seconds, while applying a pulsed magnetic field; gradient foaming control, 50℃, 25MPa maintained for 3 minutes, adding 0.05% nano-calcium carbonate for nucleation, linearly heating to 80℃, reducing pressure to 10MPa and applying axial tensile stress expansion, liquid nitrogen spray quenching and shaping; foaming expansion rate of 70% electrostatic adsorption embedded in pre-coated polyurethane glass fiber mesh, 0.1MPa air pressure compaction and pressure maintenance; S3: Curing and hole opening treatment, which is cured by 2450MHz microwave irradiation for 8 minutes and 915MHz microwave treatment for 12 minutes; ultrasonic assisted treatment after mechanical hole opening, and then chemical etching by immersing in 0.1% hydrofluoric acid solution.

2. The process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge according to claim 1, characterized in that: The first stage dehydration conditions in S1 are: temperature 100° C., vacuum degree -0.095 MPa, and time 1 hour; the second stage dehydration conditions are: temperature 80° C., vacuum degree -0.08 MPa, and time 1 hour, and the final polyol moisture content is ≤0.02 wt %.

3. The process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge according to claim 1, characterized in that: During the foaming stage, a laser particle size analyzer detects the cell size distribution online. In the subsequent curing stage, an infrared thermal imager monitors the uniformity of the temperature field and automatically adjusts the microwave power.

4. The process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge according to claim 1, wherein: The sponge is placed in a supercritical The reaction mixture was treated at a pressure of 8 MPa and a temperature of 40°C for 1 hour to remove residual catalyst and oligomers.

5. The process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge according to claim 1, wherein: The mass ratio of multi-walled carbon nanotubes, montmorillonite and silane coupling agent in the nanofiller dispersion is , and the ultrasonic treatment parameters are: frequency 40 kHz, power 300 W, time 15 min, high shear mixer speed 8000 rpm, shear time 10 min.

6. The process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge according to claim 1, characterized in that: The pulse injection in S2 The magnetic field parameters are: pulse frequency 10 Hz, magnetic field intensity 0.5 T, and an axial alternating magnetic field is applied during the pressure holding stage after each injection, with the magnetic field direction forming an angle of 30° with the axis of the reactor.

7. The process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge according to claim 1, characterized in that: In the gradient foaming control, the particle size of the heterogeneous nucleating agent nano calcium carbonate is 20-50nm, and the addition amount is 0.05-0.1% of the total mass of the polyol; the axial tensile strain rate is , the stretching direction is perpendicular to the fiber web plane.

8. The process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge according to claim 7, characterized in that: The microwave irradiation parameters in S3 are: 2450 MHz, power density 2.5 W / g, and time 8 minutes in the first stage; 915 MHz, power density 1.2 W / g, and time 12 minutes in the second stage; UV curing wavelength is 365nm, irradiation intensity .

9. The process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge according to claim 8, characterized in that: The concentration of graphene quantum dots in the spray sol is 0.1-0.3 wt %, the particle size is 2-5 nm, and the sol carrier is a mixed solvent consisting of ethanol and deionized water in a volume ratio of 3:

1.

10. The process for preparing a high-elasticity, pressure-resistant, breathable and water-permeable sponge according to claim 9, characterized in that: The chemical etching solution is a mixed acid solution composed of hydrofluoric acid and nitric acid in a volume ratio of 1:3, with a total concentration of 0.05-0.15wt% and an etching time of 30-60s. After etching, the solution is immediately neutralized and rinsed with a sodium bicarbonate solution with a pH of 8.5.

Citation Information

Patent Citations

  • Preparation method of polyurethane filter sponge

    CN111040123A

Cited By

  • Flexible cable material for robot and preparation method thereof

    CN120118509A